PENGEMBANGAN TES DIAGNOSTIK FOUR TIER TEST DILENGKAPI DENGAN SELF-DIAGNOSIS SHEET TENTANG ENERGI DI SMA - Dendodi Dendodi; Haratua Tiur Maria S; Hamdani Hamdani (Universitas Tanjungpura, 2020)
The purpose of this research is to produce a qualified diagnostic test that can be used to discover students’ misconceptions about energy in high school’s 10th graders. This research uses Research and Development (R&D) with the form of four tier test. The development of diagnostic test uses the adoption of Borg & Gall development steps that has been simplified into seven steps. The inisial design consists of twelve item of test of multiple choices. The trial step of this diagnostic test was done to 35 students in the in the small scale trial, and 91 students in the large scale trial. According to the data analysis, it can be concluded that the developed diagnostic test is qualified of the use to discover students’ misconceptions, because: 1) has higher validity than table validity, 2) has of reliabily of 0,783, 3) all items of the diagnostic can discover students’ misconceptions, 4) has a diffuculty index 0,38, 5) the level of readability of the questions 0,63. The qualified items that worth of use of this test are twelve items